Latest information in relation to Postpartum Dysgalactia Syndrome of sows - PAPATSIROS (Β.Γ. ΠΑΠΑΤΣΙΡΟΣ) V. G.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
The «Postpartum Dysgalactia Syndrome» (PPDS), that is referred in literature as «Periparturient Hypogalactia Syndrome» (PHS), causes important economical losses in die global swine industry. The aetiology of syndrome includes endotoxins and generally die negative, as well as some positive gram bacteria (colibacteroides, ß-haemolytic streptococci G and L, staphylococci, Arcanobacterium pyogenes, Proteus, Bacteroides, Clostridium and Haemophilus). Moreover, several aetiological agems of functional hypoagalactia, factors associated widi stress of sows and conditions that contribute in the proliferation of bacteria and consequendy in the potential endotoxemia (e.g. cystitis, metritis, vaginitis, constipation, mastitis), seem to play a significant role. Risk factors that are often suspected for PPDS are the health status of sows (Fat Sow Syndrome-¥SS, extended duration of parturition, post-partum pyrexia, teat malformation and injuries, as well as hypoplasia of mammary glands), the housing and management conditions of the sow around parturition (slippery floors, hygiene, temperaturehumidity of rooms, reduced activity of the sows, watering system), as well as diet composition (concentration of fiber, proteins, vitamin E and selenium). The clinical signs are characterized mainly by disorders of lactation and health status of sows (anorexia, depression, pyrexia, constipation and abnormal postpartum vulval discharge), as well as from decreased litter performance (unsuccessful attempts for suckling, intense discomposure, diarrhoea, poor growth rates, unevenness of litters regarding to body weight of piglets, increase of preweaning mortality).